2008
DOI: 10.1016/j.jeem.2007.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Trade, politics, and the environment: Tailpipe vs. smokestack

Abstract: The vast majority of economic research on environmental regulation in open economies focuses on producer generated-''smokestack''-pollution; we instead consider consumer generated-''tailpipe''-pollution. We examine how political opposition to environmental regulation varies with a country's trade regime, and show that the impact on environmental policy of a move from autarky to free trade can depend critically on who ultimately generates pollution, producers or consumers. We find that opening to trade may rais… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(54 citation statements)
references
References 22 publications
3
51
0
Order By: Relevance
“…In such circumstances, developed countries attain benefits from trade openness at the cost of environment in developing economies. Copeland and Taylor, [26] [34] reported that trade affects environment significantly and same view is confirmed by Frankel, [35].…”
Section: Literature Reviewsupporting
confidence: 52%
“…In such circumstances, developed countries attain benefits from trade openness at the cost of environment in developing economies. Copeland and Taylor, [26] [34] reported that trade affects environment significantly and same view is confirmed by Frankel, [35].…”
Section: Literature Reviewsupporting
confidence: 52%
“…In most respects the development of these inventories has been based on a production or "smokestack" principle focusing, for example, on where carbon dioxide emissions are actually produced, rather than focusing on how these emissions are connected to household consumption activity. Indeed, one vein of economic research on the regulation and measurement of environmental externalities has argued that there has been too much focus on the producer ("smoke-stack") as opposed to consumer generated ("tailpipe") pollution (see for example, McAusland, 2008).…”
Section: Background and Contextmentioning
confidence: 99%
“…In the conclusions we argue that our understanding of regional jurisdiction matters in the implementation of environmental policies. Furthermore the impact of interventions critically depends on who ultimately is understood to be generating pollution, be it producers or consumers or indeed some combination of the two (see also McAusland, 2008;Gallego and Lenzen, 2005).…”
Section: Insert Figure 1 About Herementioning
confidence: 99%
“…Trade will also affect the market for new durable goods indirectly by increasing resale prices in high-income countries and decreasing resale prices in low-income countries. 7 A similar distinction between consumption and production is made by McAusland (2008) which examines theoretically how opposition to environmental regulations varies with whether pollution is generated by producers or consumers.…”
Section: The Environmental Consequences Of This Pattern Of Tradementioning
confidence: 99%